THE CONSTITUTIONAL AND LEGAL BASIS FOR THE COOR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines in detail the role of science in the development of society and the state. The role of the Academy of Sciences, which coordinates the development of fundamental and applied sciences, is emphasized. The article substantiates the urgent need to rethink traditional approaches to scientific development.
Keywords: Academy of Sciences, fundamental and applied sciences, laws, coordination, scientific research.